PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN - Linda, Wulan Mey; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to test the influence of profitability, firm size, and ownership structure to the firm value.The population of this research is pharmaceutical companies which are listed in the IDX. Profitability has beenmeasured by using Return on asset; firm size has been measured by using total asset; and ownership structuralhas been measured by using the amount of stock ownership, whereas the firm value is based on the stock price.The research samples are pharmaceutical companies which are listed in Indonesia Stock Exchange (IDX) in2011-2014 periods and these companies have been selected by using purposive sampling. 8 pharmaceuticalcompanies have been selected as samples. The source of secondary data has been obtained from IndonesianCapital Market Directory and Indonesia Stock Exchange Corner and the official website of Indonesia StockExchange i.e. www.idx.co.id. The analysis method has been carried out by using multiple linear regressionsanalysis. The result of this research shows that profitability, firm size, managerial ownership, domesticinstitution ownership, foreign institution ownership and public ownership have significant influence to the firmvalue.Keywords: Profitability, firm size, ownership structure, firm value.